Tuning d-band centers by coupling PdO nanoclusters to WO3 nanosheets to promote the oxygen reduction reaction. Issue 27 (2nd July 2020) - Lee, Jun-Hyeong; Yim, DaBin; Park, Jung Hyun; Lee, Chi Ho; Ju, Jong-Min; Lee, Sang Uck; Kim, Jong-Ho
Abstract : The direct conversion of 1T-WS2 into WO3 nanosheets by spontaneous deposition of PdO nanoclusters produces a PdO@WO3 S x electrocatalyst for the ORR. Abstract : Supporting Pd on a metal oxide is an effective way to modulate its electronic structure to enhance its electrocatalytic activity in the oxygen reduction reaction (ORR). However, strong coupling between Pd and metal oxides typically requires high-temperature synthesis or annealing. Here, we report a mild and effective approach for synthesis of PdO nanoclusters coupled to WO3 nanosheets (PdO@WO3 S x ) via direct conversion of metallic 1T-WS2 nanosheets into WO3 by spontaneous deposition of PdO onto the nanosheets in H2 O at 50 °C for 1 h. Strong coupling in as-prepared PdO@WO3 S x was confirmed by observing shifts in binding energy compared to those of pure PdO and WO3 . 1T-MoS2 nanosheets were partially converted into MoO3 in an analogous reaction to produce the hybrid MoS x O3 but in low yield due to preferential dissolution forming aqueous MoO4 2− . The hybrid PdO@WO3 S x exhibited higher half-wave potential (0.89 V vs. RHE) and limiting current density (−6.24 mA cm −2 ) in the ORR than both PdO@MoS x O3 and commercial Pt/C. In addition to its higher electrocatalytic activity, PdO@WO3 S x showed greater durability compared to Pt/C in the electrocatalytic activity during the continuous ORR. Computational simulations based on d-band center theory reveal that the d-band center of Pd in PdO@WO3 S x was upshifted to −2.57 eV, very close to that of Pt. This Pt-like d-band center of PdO@WO3 S x enabled its excellent electrocatalytic activity in the ORR. This work presents a facile approach to the synthesis of PdO hybrid catalysts and provides fundamental insight into their enhanced electrocatalytic activity for the ORR.